1951
DOI: 10.1136/hrt.13.4.503
|View full text |Cite
|
Sign up to set email alerts
|

The Radiology of Acute Pulmonary Oedema

Abstract: The purpose of this paper is to describe some of the X-ray appearances of acute pulmonary cedema occurring in heart failure, and to distinguish them from other shadows in the lung commonly associated with heart disease. It is based on films of patients taken during attacks of breathlessness due to acute pulmonary cedema. The films were usually taken in the ward with a portable X-ray apparatus, a procedure causing little discomfort to the patient, though with the inherent disadvantages of a short tube-distance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1955
1955
2000
2000

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…In this context some important information has been obtained from studies of pulmonary oedema and vascular changes associated with mitral stenosis. It is known that central pulmonary oedema may complicate mitral III R. T. Hughes stenosis (Jackson, 1951), especially in pregnancy, but rarely when long-standing heart failure is associated with gross left ventricular dilatation. In a pathological study Parker (1958) found that central pulmonary congestion occurs when arterial changes are minimal.…”
Section: Associated Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context some important information has been obtained from studies of pulmonary oedema and vascular changes associated with mitral stenosis. It is known that central pulmonary oedema may complicate mitral III R. T. Hughes stenosis (Jackson, 1951), especially in pregnancy, but rarely when long-standing heart failure is associated with gross left ventricular dilatation. In a pathological study Parker (1958) found that central pulmonary congestion occurs when arterial changes are minimal.…”
Section: Associated Symptomsmentioning
confidence: 99%
“…This was true in one of Doniach's cases, and similarly Bass and Singer (1950) found that extensive shadows might disappear when left ventricular failure was alleviated. NON-SPECIFICITY It has been made abundantly clear in the literature that the butterfly density is not specific to uraemia (Doniach, 1949;Jackson, 1951). It is recognized as the classical appearance of acute pulmonary oedema (Nessa and Rigler, 1941) and it occurs almost invariably in patients in whom an attack of severe dyspnoea complicates an illness in which strain is being thrown on the left side of the heart (Hodson, 1950).…”
mentioning
confidence: 99%
“…Jackson [9] did not find any unilateral presentation in a re view of 20 cases. Gleason and Steiner [7] found 6 cases with an unilateral pattern in the same number of patients.…”
Section: Discussionmentioning
confidence: 99%